Nanotechnology in Construction 3 2009
DOI: 10.1007/978-3-642-00980-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Modification of Cementitious Materials

Abstract: Abstract. This research investigates changes in the nanostructure and the nanoscale local mechanical properties of cement paste with micro-and nano-modifiers. Silica fume and multiwall carbon nanotubes (MWCNTs) were used as micro-and nano-modifiers. An effective method of dispersing CNTs in cement matrix was developed. A detailed study on the effects of CNTs concentration and aspect ratio on the fracture properties, nanoscale properties and microstructure of nanocomposite materials, was conducted. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 12 publications
4
61
1
2
Order By: Relevance
“…This remains the challenge for high performance composite applications [18][19][20][21]. Many studies in the recent past have demonstrated the compatible dispersion, surface functionalization, andchanges in surface energy of the nanotube with the goal oftapping the tremendous potential of CNTs as a reinforcing material for high performance cementitious composites [11,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This remains the challenge for high performance composite applications [18][19][20][21]. Many studies in the recent past have demonstrated the compatible dispersion, surface functionalization, andchanges in surface energy of the nanotube with the goal oftapping the tremendous potential of CNTs as a reinforcing material for high performance cementitious composites [11,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These aggloromates decrease the linkage of nano particles with the binding phase of concrete. In order to enhance the bonding and to increase the nano materials dispersion, it is recommended to add super plasticiser, and ultrasonification [8,[18][19][20]. Vishwakarma et al (2016) [4] used nano-particles size (~50-70 nm) of Rice Husk Ash (RHA) agricultural waste as a partial replacement of Ordinary Portland Cement.…”
Section: Nano-materials In Concrete Mixturesmentioning
confidence: 99%
“…In particular, the superior electrical and mechanical properties of nanoengineered powders, such as nanotubes and nanofibers, has resulted in several demonstrations of conductive cementitious materials with excellent sensing capabilities [1,2]. Such materials offer great promise at the monitoring of large- 2 of 18 scale systems, or mesosystems, because they can form large-scale structural components comprising an infinite set of mechanically robust sensors that can be used to measure static and dynamic strain, from which strain-based and vibration-based structural health monitoring (SHM) can be conducted [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among other carbon-based fillers [15,16], carbon nanotubes (CNTs) showed promise for several applications [17][18][19][20][21]. For example, such particles can be used to provide conductive capability to insulating materials, leading to the creation of self-sensing materials [22,23]. Self-sensing materials find great potential in the field of SHM.…”
Section: Introductionmentioning
confidence: 99%